Determinism And Freedom Reflected In David Nicholls's One Day Novel (2009): A Philosophy Of Determinism - Wijayanti, Linda Ari; , Drs. H. AbdillahNugroho, M. Hum; , Siti Fatimah, S. Pd, M. Hum (2013)
This study is about determinism and freedom in One Day novel. The objective of this study are to analyze the novel based on its structural elements and apply the determinism approach to analyze the determinism and freedom in One Day novel. The data source comes from primary data source that is the novel and the secondary data sources are references and data or materials related to the research picking up from the books and the internet related with the novel. The method of the data collection is descriptive analysis.The researcher uses Barret's major point of determinism and freedom to answer the problem of the study. The study is descriptive qualitative research whose data are taken from novel. The technique of the collecting data is library research, while the technique of analyzing data is descriptive. The study comes to the following conclusions. Firstly, based on the structural analysis of each elements, it shows that character and characterization, setting, plot, point of view, and theme are related to each other and form the unity. Secondly, based on the determinism analysis the writer wants to say that humans only have the freedom to choose and do all they want, and they can only hope and strive in order that their desires could be achieved and their hopes come true, sometimes what they choose and what they do give a major influence on their future or the rest of their lives but on the other hand everything is determined by God, including, life and death, fate and destiny, fortune and mate.